Frequency of BCR-ABL1, E2A-PBX1, MLL-AF4, and TEL-AML1 fusion genes in B-cell acute lymphoblastic leukemia - Sánchez-Pinto, Francisco (2023)
Objective. To describe the frequency of BCR-ABL1, E2A-PBX1, MLL-AF4, and TEL-AML1 fusion genes in patients with B-cell acute lymphoblastic leukemia at the Instituto Nacional de Salud del Niño of San Borja, Lima (Peru). Methods. We studied 375 samples from pediatric patients diagnosed with B-cell acute lymphoblastic leukemia, received at the Genetics Service, in which BCR-ABL1, E2A-PBX1, MLL-AF4, and TEL-AML1 fusion genes were detected in bone marrow or peripheral blood, using reverse transcriptase polymerase chain reaction (RTPCR). Results. Of the total samples, 58 were positive for BCR-ABL1, E2A-PBX1, MLL-AF4, and TEL-AML1 fusion genes, which had the following frequencies: 2.13%, 4.53%, 0.53%, and 8.27%, respectively. Conclusions. The TEL-AML1 fusion gene is the most frequent in our pediatric population, which is associated with a favorable prognosis.